Culture, intermarriage, and differentials in second-generation immigrant women's labor supply - Z. Eylem Gevrek; Deniz Gevrek; Sonam Gupta (Institute for the Study of Labor (IZA), 2011)
We examine the impact of culture on the work behavior of second-generation immigrant women in Canada. We contribute to the current literature by analyzing the role of intermarriage in intergenerational transmission of culture and its subsequent effect on labor market outcomes. Using relative female labor force participation and total fertility rates in the country of ancestry as cultural proxies, we find that culture matters for the female labor supply. Cultural proxies are significant in explaining number of hours worked by second-generation women with immigrant parents. More importantly, we show that the impact of cultural proxies is significantly larger for women with immigrant parents who share same ethnic background than for those with intermarried parents. The fact that the effect of culture is weaker for women who were raised in intermarried families stresses the importance of intermarriage in assimilation process. Our results are robust to different specifications and estimation strategies.
urn:nbn:de:101:1-201110263871
Keywords: J12; J16; J22; J61; 330; culture; labor supply; immigrant women; intermarriage; Weibliche Arbeitskräfte; Arbeitsangebot; Migranten; Wirtschaftskultur; Ehe; Schätzung; Kanada